DEFiNE: A Method for Enhancement and Quantification of Fluorescently Labeled Axons - Powell, Jeanne M.; Plummer, Nicholas W.; Scappini, Erica L.; Tucker, Charles J.; Jensen, Patricia (Frontiers in Neuroanatomy, 2019)
Visualization and quantification of fluorescently labeled axonal fibers are widely employed in studies of neuronal connectivity in the brain. However, accurate analysis of axon density is often confounded by autofluorescence and other fluorescent artifacts. By the time these problems are detected in labeled tissue sections, significant time and resources have been invested, and the tissue may not be easy to replace. In response to these difficulties, we have developed DEFiNE (Digital Enhancement of Fibers with Noise Elimination), a method for eliminating fluorescent artifacts from digital images based on their morphology and fluorescence spectrum, thus permitting enhanced visualization and quantification of axonal fibers. Application of this method is facilitated by a DEFiNE macro, written using ImageJ Macro Language (IJM), which includes an automated and customizable procedure for image processing and a semi-automated quantification method that accounts for any remaining local variation in background intensity. The DEFiNE macro is open-source and used with the widely available FIJI software for maximum accessibility.